Sorption of hydrophobic organic compounds to a diverse suite of carbonaceous materials with emphasis on biochar. (February 2016) - Kupryianchyk, Darya; Hale, Sarah; Zimmerman, Andrew R.; Harvey, Omar; Rutherford, David; Abiven, Samuel; Knicker, Heike; Schmidt, Hans-Peter; Rumpel, Cornelia; Cornelissen, Gerard
Abstract: Carbonaceous materials like biochars are increasingly recognized as effective sorbent materials for sequestering organic pollutants. Here, we study sorption behavior of two common hydrophobic organic contaminants 2, 2′, 5, 5′-tetrachlorobiphenyl (CB52) and phenanthrene (PHE), on biochars and other carbonaceous materials (CM) produced at a wide range of conditions and temperatures from various feedstocks. The primary aim was to establish structure–reactivity relationships responsible for the observed variation in CM and biochar sorption characteristics. CM were characterized for their elemental composition, surface area, pore size distribution, aromaticity and thermal stability. Freundlich sorption coefficients for CB52 and PHE (i.e. Log K F, CB52 and K F, PHE, respectively) to CM showed a variation of two to three orders of magnitude, with Log K F, CB52 ranging from 5.12 ± 0.38 to 8.01 ± 0.18 and Log K F, PHE from 5.18 ± 0.09 to 7.42 ± 1.09. The highest Log K F values were observed for the activated CM, however, non-activated biochars produced at high temperatures (>700 °C) sorbed almost as strongly (within 0.2–0.5 Log units) as the activated ones. Sorption coefficients significantly increased with pyrolysis temperature, CM surface area and pore volume, aromaticity, and thermal stability, and decreased with H/C, O/C, (O + N)/C content. The results of our study contribute to the understanding of processes underlying HOC sorption to CM and explore the potential of CM as engineered sorbents for environmental applications. Graphical abstract: Highlights: Biochar plays a crucial role in transport and fate of organic contaminants. The multiple factors involved in sorption of HOCs to biochar are investigated. Variations in sorptive ability are related to physico-chemical properties of biochars.